2021
DOI: 10.3390/ijerph18147574
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reactions among Children with Tuberculosis in Tashkent, Uzbekistan, 2019

Abstract: The treatment of childhood tuberculosis can be challenging due to the lack of pediatric drug formulations and monitoring of drug-toxicity in routine settings. There are no published studies from Uzbekistan on the adverse drug reactions (ADR) associated with anti-tuberculosis treatment in children. In this study, we aimed to investigate the ADR associated with anti-tuberculosis treatment in children. This was a cohort study using secondary program data of children treated at the city and regional tuberculosis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…During observation, side effects occurred in the intensive phase, consistent with findings from a study by Abdusalomova M. et al This study identified gastrointestinal complaints as the most frequent side effects in children. 15 In this case, our patient exhibited nausea without vomiting during the first two weeks of therapy. Taking ATD APGHN at night, as described in the same study, can be a helpful strategy to manage these gastrointestinal side effects, which often improve without medication.…”
Section: Side Effects Of Atdmentioning
confidence: 62%
“…During observation, side effects occurred in the intensive phase, consistent with findings from a study by Abdusalomova M. et al This study identified gastrointestinal complaints as the most frequent side effects in children. 15 In this case, our patient exhibited nausea without vomiting during the first two weeks of therapy. Taking ATD APGHN at night, as described in the same study, can be a helpful strategy to manage these gastrointestinal side effects, which often improve without medication.…”
Section: Side Effects Of Atdmentioning
confidence: 62%
“…There is a limited number of pharmaceutical formulations that can be reliably used to treat TB in children. Other issues include a lack of information on the toxicity of drugs and unpredictable levels of adherence to treatment [ 16 ]. Preventive medications have shown to reduce the development of active TB disease by 91% among infected children if they are treated prior to experiencing TB symptoms [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…По данным литературных источников у 30-55 % детей и подростков в процессе лечения туберкулеза развиваются побочные реакции (ПР) [1][2][3][4][5][6]. При лечении пациентов с лекарственно-устойчивым туберкулезом с применением резервных препаратов частота ПР значительно возрастает по сравнению с использованием в режиме лечения только основных противотуберкулезных препаратов (ПТП) с 30,0 % до 78,0 % [7][8][9][10].…”
Section: Introductionunclassified